Family medicine research: seizing the moment to advance the field - Brad Wright; Aoife O’Connor; Erin P. Fraher; Miguel Marino; Bianca K. Frogner (BMC Health Services Research)
Abstract Despite a growing awareness that primary care is essential to an accessible, equitable, high-quality, cost-effective health care system, family medicine research remains woefully underdeveloped. The increased focus of both state and federal policy makers on primary care payment and care delivery models presents an opportunity for family medicine to redefine itself as an academically rigorous discipline at the forefront of generating evidence that improves patient care and population health while reducing costs. In a critical review of the literature, we identified five themes—leadership, funding, resources, team science, and departmental culture—that are integral to family medicine departments seeking to grow and expand their research capacity.